Mortality of women with ST-segment elevation myocardial infarction and cardiogenic shock – results from the PL-ACS registry - Kołodziej, Małgorzata; Kurzawski, Jacek; Janion-Sadowska, Agnieszka; Gierlotka, Marek; Poloński, Lech; Gąsior, Mariusz; Sadowski, Marcin (Medical Studies/Studia Medyczne, 2016)
Introduction: Gender-related differences are well elucidated in ST-segment elevation myocardial infarction (STEMI) patients. However, data on patients with cardiogenic shock (CS) are scarce and do not indicate the cause-effect relationship. Aim of the research : To evaluate the differences between women and men with CS complicating STEMI and to identify factors which determine the prognosis in the female group. Material and methods : A total of 3589 consecutive patients with CS were selected from a large, multicenter national registry on 57 400 consecutive STEMI patients. Results : Women had a greater time delay from symptom onset to treatment (admission within the first 2 h, 37.1% vs. 44.8%; p < 0.001). They were also less likely to undergo interventional treatment (40.4% vs. 48.1%; p < 0.001) and to receive coronary stenting (86.8% vs. 90.1%; p = 0.045), glycoprotein IIb/IIIa inhibitors (15.3% vs. 20.1%; p < 0.001) and clopidogrel (46.3% vs. 53.6%; p < 0.001). In the female patients in-hospital and 12-month mortality were higher than in their male counterparts (55% vs. 45.8%; p < 0.001 and 72.5% vs. 63.8%; p < 0.001, respectively). Women with cardiogenic shock were less likely to receive optimal therapy than men, which resulted in a poor clinical outcome. Conclusions : This should encourage medical professionals to apply advanced therapeutic strategies without gender bias. Only if there are no gender-related discrepancies in the management of patients with cardiogenic shock may the beneficial impact of invasive treatment be fairly assessed and the hypothesis that more guideline-adherent treatment of women results in better outcomes be validated.